Analisis Faktor Determinan Yang Mempengaruhi Ketahanan Pangan di Indonesia Tahun 2019-2022 - Putri, Binari Exacta; S, Suripto (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Food security is a good indicator to determine the socio-economic conditions of a country. A person's ability to buy a product and service is determined by his income. Every human being needs to fulfill their needs for clothing, food and shelter. Despite its status as an agricultural country, Indonesia is still plagued by food security problems. Data released by FAO shows that Indonesia has at least 22.9 million people affected by hunger. Then, Indonesia's ranking is still far from the food security index ranking, namely 63 out of 113 countries. This research aims to conduct a scientific analysis of the factors that influence food security in Indonesia. The research method used is Seemingly Unrelated Regression (SUR) for the 2019-2022 period. The research results show that all per capita expenditure variables and rice production have a positive and significant effect on food security, and poverty variables and population growth variables have a negative and significant effect on food security.